Uji Aktivitas Senyawa Antibakteri Katak Papua (ANTIBACTERIAL ACTIVITY TEST OF PAPUAN FROGS) - Massora, Maria; Kawulur, Elda Irma J. J.; Abubakar, Hermawaty (Jurnal Veteriner; Vol 19 No 1 (2018), 2018)
Skin and submental glands of Papuan frogs have antibacterial compounds‘ which were capable to impede growth of tested bacteria based on diffusion method. These frogs were Platymantis papuensis , Litoria infrafrenata , Bufo melanostictus , Rana grisea and Rana sp., and the tested bacterial were the positive Gram bacteria ( Staphylococcus aereus , and Bacillus subtilis ) and the negative Gram bacteria ( Escherichia coli and Pseudomonas aeroginosa ). Skin frog which extracted with hot water (100oC) showed antibacterial activity which significantly impeded the growth of tested bacteria using diffusion method.